2013
DOI: 10.1093/intqhc/mzt009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a checklist on the quality of post-anaesthesia patient handover: a randomized controlled trial

Abstract: This study suggests that the use of a checklist for post-anaesthesia handover might improve the quality of patient handover by increasing the information handed over.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 17 publications
3
57
1
Order By: Relevance
“…Checklists help in managing information without missing important patient data (Salzwedel et al, 2013), improve the quality of handover process and enhance quality of care and patient safety (WHO, 2007;Matic et al, 2011). A study (Pothier, 2005), examining three different methods of handoff, found that the one demonstrating the greatest amount of information retention involved utilisation of a pre-printed sheet containing patient information with verbal report (96%-100%), followed by note taking and verbal report method (31%-58%), and lastly, only verbal report (0-58%).…”
Section: Discussionmentioning
confidence: 99%
“…Checklists help in managing information without missing important patient data (Salzwedel et al, 2013), improve the quality of handover process and enhance quality of care and patient safety (WHO, 2007;Matic et al, 2011). A study (Pothier, 2005), examining three different methods of handoff, found that the one demonstrating the greatest amount of information retention involved utilisation of a pre-printed sheet containing patient information with verbal report (96%-100%), followed by note taking and verbal report method (31%-58%), and lastly, only verbal report (0-58%).…”
Section: Discussionmentioning
confidence: 99%
“…(1) Information communicated in the handover process should include perioperative anaesthetic and surgical issues, as well as recommended postoperative management. (2) The challenge is further increased in a setting where paediatric patients have complex surgical and medical issues, and interdisciplinary communication occurs between the outgoing anaesthetic team and incoming paediatric intensive care team. (3) Over the years, various handover techniques have been established to provide continuity of patient care during change of shift, (4) interdisciplinary referral, (4,5) postsurgical care from the OT to ICU (6) and ward transfer of a patient.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Over the years, various handover techniques have been established to provide continuity of patient care during change of shift, (4) interdisciplinary referral, (4,5) postsurgical care from the OT to ICU (6) and ward transfer of a patient. (7) Techniques such as narrative face-to-face communication, (3,8) standardised protocols, (1,2,5) and written documents (1,2) have been used in the handover process. In many institutions worldwide, handover documents have been shown to be a useful tool in the process, as they maximise communication during the handover.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations